"Children and Their Schools at the Quadcentennial" - Irwin Hyman; Sherone Sherone Levow Maital (Journal of Clinical Child Psychology 9.2 (Summer 1980):, 1980)
Two scenarios of future education, eutopian and dystopian. The dystopian system is all technology in isolation and is controlled by corporations. The eutopian system focuses on family life and the rights of children, is well-funded, and teachers all hold doctorates and schools have no administrators.
Keywords: Female author; Israeli author; Male author; US author